2003
DOI: 10.1007/bf02491762
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycleversus podant-type neutral ionophore in potentiometric detection of mucolytic agents following separation by various HPLC modes

Abstract: SummaryPotentiometrTc detection of lipophTlic drugs such as clenbuterol, ambroxol and bromhexine in standard bore cyano and narrow bore hybrid, reversed phase HPLC systems was developed to enable specific determination of these mucolytic agents in some marketed oral formula tions. The macrocycle and podant type, neutral ionophores, respectively: hexaks(2,3,64ri O octyl) ~ cyclodextrin (CDX) and N,N,N',N'4etracyclohexyl oxybis(o phenyleneoxy)diaceta mide flOPA), were used to construct PVC based, liquid membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(77 reference statements)
2
5
0
Order By: Relevance
“…Based on the results of potentiometric detection with the MPI_Comp electrode developed here the analyzed male urine sample contains 46.3 lM DHEAS, and 3.17 lM ADS, while the analyzed female urine sample contains 29.4 lM DHEAS and 6.92 lM ADS. The satisfactory RSD of the intra-and interday assays for these average values (n = 6) of both analytes were obtained, i.e., below 6 and 18%, respectively, which is comparable with repeatability and reproducibility observed previously for the determination of mucolytic drugs by HPLC with potentiometric detection [18,34]. The obtained calibration curves of the MPI_Comp electrode (see Fig.…”
Section: Direct Analysis Of Urine Biosamples: a Pilot Studysupporting
confidence: 86%
See 2 more Smart Citations
“…Based on the results of potentiometric detection with the MPI_Comp electrode developed here the analyzed male urine sample contains 46.3 lM DHEAS, and 3.17 lM ADS, while the analyzed female urine sample contains 29.4 lM DHEAS and 6.92 lM ADS. The satisfactory RSD of the intra-and interday assays for these average values (n = 6) of both analytes were obtained, i.e., below 6 and 18%, respectively, which is comparable with repeatability and reproducibility observed previously for the determination of mucolytic drugs by HPLC with potentiometric detection [18,34]. The obtained calibration curves of the MPI_Comp electrode (see Fig.…”
Section: Direct Analysis Of Urine Biosamples: a Pilot Studysupporting
confidence: 86%
“…The applied flow rate was 1 mL/min. A Shimadzu UV -Vis detector (SPD-10Avp/10AVvp) (260 nm), and "wall-jet" type potentiometric flow cell constructed in the laboratory [34] were used in series. The jet-to-electrode distance was 100 lm.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a detailed study on the lifetimes, robustness, and reliability of the PVC-based membrane CWE electrode in acetonitrile/dilute acid conditions were described in our earlier reports [30,50]. Similarly, we observed that the activity of the TCPB-based CWE electrode used here was reduced to 75% of its initial level (measured as peak area of bufuralol) after continuous use in applied CE conditions during three weeks.…”
Section: 10610supporting
confidence: 61%
“…As the diameter of copper wire was reduced here by a factor of 2.5, this improvement in the detection limit of dopamine is probably related to the use of acetonitrile in BGE and its lower pH*. The effect of acetonitrile as a component of the acidic mobile phase on the greatly increased response of the PVC-based CWE under nano-HPLC conditions has already been described [50]. The LOD observed here for dopamine was also improved in comparison with the millimolar LOD reported by Kappes et al [18] in CE with a 90 lm platinum wire PVC-based CWE and a content of the non-specific cation exchanger TCPB increased to 3.4%, o-nitrophenyl octyl ether (NPOE) as the low-hydrophobicity (log P = 5.9 [31]) and high resistance (e r = 23.9 [31]) plasticiser, and tartaric acid as BGE component.…”
Section: Analytical Performance Of Potentiometric Detectionmentioning
confidence: 93%